PENGARUH KOMPETENSI, PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPENSASI TERHADAP KINERJA ACCOUNT REPRESENTATIVE DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Afrina Afrina; Vince Ratnawati; Poppy Nurmayanti; Fitri Yunina (Jurnal Inovasi Penelitian, 2021)
This research aims to analyze the effect of competency, use of information technology, compensation and organizational commitment as a moderating variable and its impact on Account Representative performance. The proposed hypothesis: Competency has a significant effect on Account Representative performance, use of technology information has a significant effect on Account Representative performance, compensation has a significant effect on Account Representative performance and organizational commitment as a moderating variable between the effect of competency, use of information technology and compensation to the Account Representative performance. The result of the research shows that competency has positive and significant effect to Account Representative performance, use of technology information has no significant effect to Account Representative performance, compensation has no significant effect to Account Representative performance, organizational commitment doesn’t moderate effect of competency to Account Representative performance, organizational commitment doesn’t moderate effect of use of technology information and organizational commitment doesn’t moderate effect of compensation to Account Representative performance to Account Representative performance.